Metagenomic next-generation sequencing-assisted diagnosis of a rare case of primary cutaneous acanthamoebiasis in an HIV patient: a case report - Fan, Wei; Li, Pin; Wei, Qihao; Liu, Xinru; Cai, Yuxiang; Li, Bin; Lu, Yaping (Frontiers in Cellular and Infection Microbiology, 2024)
Pathogenic and free-living Acanthamoeba are widely distributed in the environment and have been reported to cause keratitis and universally fatal encephalitis. Primary cutaneous acanthamoebiasis caused by Acanthamoeba is exceedingly rare and presents as isolated necrotic cutaneous lesions without involvement of the cornea or central nervous system. Cutaneous acanthamoebiasis often occurs in immunocompromised patients and is likely overlooked or even misdiagnosed only by cutaneous biopsy tissue histopathological analysis. Here, we report a HIV-infected 63-year-old female with oral leukoplakia for 4 months and scattered large skin ulcers all over the body for 2 months. The cause of the cutaneous lesions was unclear through cutaneous specimens histopathological analysis, and subsequently Acanthamoeba were detected by metagenomic next-generation sequencing (mNGS), which may be the cause of cutaneous lesions. Based on the mNGS results, a pathologist subsequently reviewed the previous pathological slides and found trophozoites of Acanthamoeba so that the cause was identified, and the skin ulcers improved significantly after treatment with multi-drug combination therapy. Acanthamoeba is also a host of pathogenic microorganisms. The presence of endosymbionts enhances the pathogenicity of Acanthamoeba, and no other pathogens were reported in this case. mNGS is helpful for rapidly diagnosing the etiology of rare skin diseases and can indicate the presence or absence of commensal microorganisms.